The Effectiveness of Quiz Demonstration Practice Revision (QDPR) Model in Helping Students’ English Pronounciation - Abdul Latif; Jupri Jupri (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2021)
The study examined the effectiveness of Quiz Demonstration Practice Revision (QDPR) in helping students’ English pronunciation. There were two research questions in the study; 1) Is Quiz Demonstration Practice Revision (QDPR) model effective in helping students’ English pronunciation?, and 2) How Quiz Demonstration Practice Revision (QDPR) model is effective in helping students’ English pronunciation? To answer the research questions, the present researcher designed the study using an experimental quantitative research. The present researcher determined all of X grade students at MA. Tarbiyatul Muslimin Dasan Maalan as the population of the study and took 50 students as the sample of the study; 25 students as an experimental group and 25 students as a control group. In collecting the data of the study, the present researcher presented a test that as an instrument of the study. In analyzing the data, the present researcher calculated it using SPSS 16.0. The result of the study revealed the mean score in pre-test was 49.64 and the mean score was 73.68, while the control group, the mean score in pre-test was 71.60 and the mean score was 72.88. This means that Quiz Demonstration Practice Revision (QDPR) model is effective in helping students’ English pronunciation. Furthermore, the result of Paired Sample t-test in Sig. (two-tailed) is .000 which is lower than the significant level .005. It means that Quiz Demonstration Practice Revision (QDPR) model is significantly effective in helping students’ English pronunciation. Therefore, Quiz Demonstration Practice Revision (QDPR) model can be implemented in helping students’ English pronunciation especially senior high school students.